Fracture evaluation of plasticized polylactic acid / poly (3-HYDROXYBUTYRATE) blends for commodities replacement in packaging applications - Iglesias Montes, Magdalena Luz (2020)
Nowadays, scientific and technological efforts are being carried out to diminish serious ecological problems caused by indiscriminate use of non-biocompostable polymers in the packaging industry. In this sense, novel biodegradable blends of different composition based on poly(lactic acid) (PLA), poly(3-hydroxybutyrate) (PHB) and tributyrin (TB) are developed and here proposed as an eco-friendly alternative. Materials are characterized by fracture experiments under quasi-static and biaxial impact loading. Fracture behavior is analyzed together with thermal, tensile and water permeation properties to evaluate their potential in-service performance. TB_PLA/PHB blends with 15 wt% TB exhibit better permeation and fracture toughness than currently used bio-based polymers, being in the range of polyethylene properties. Results highlight the potential of these new blends broadening the current application field of PLA.